2010
DOI: 10.3177/jnsv.56.27
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Bone Mineral Density to Vitamin D Receptor Gene Polymorphism and Lifestyle Factors in Japanese Female Workers Aged 22-44 Years: A Cross-Sectional Study

Abstract: Summary Bone mineral density (BMD) reflects both genetic and lifestyle factors. The aim of this cross-sectional study was to investigate the influence of vitamin D receptor ( VDR ) gene polymorphism and lifestyle factors on BMD in premenopausal female workers. The subjects were 162 premenopausal female employees aged 22-44 y who worked at a large-scale integrated manufacturing facility in Japan. BMD was measured at the nondominant radius by dual energy X-ray absorptiometry. Lifestyle information was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Of the 317 subjects, 247, 68, and 2 had the TT, TC, and CC polymorphisms (77.9%, 21.5%, and 0.6%), respectively. This distribution was consistent with the reported data on the Japanese population 20,21) . No significant difference in the bone mass (OSI) was observed between the VDR gene polymorphism (rs731236) (TT versus TC + CC).…”
Section: Statistical Processingsupporting
confidence: 93%
See 1 more Smart Citation
“…Of the 317 subjects, 247, 68, and 2 had the TT, TC, and CC polymorphisms (77.9%, 21.5%, and 0.6%), respectively. This distribution was consistent with the reported data on the Japanese population 20,21) . No significant difference in the bone mass (OSI) was observed between the VDR gene polymorphism (rs731236) (TT versus TC + CC).…”
Section: Statistical Processingsupporting
confidence: 93%
“…One problem inherent in these studies is that they tend to focus solely on gene polymorphisms while disregarding the impact of lifestyle habits, such as the intake of nutrients and impact of exercise. In particular, regarding Japanese women, little data is available on the correlation between VDR polymorphisms and lifestyle habits: the intake of nutrients and impact of exercise 21) . Therefore, the aim of the present study was to identify VDR gene polymorphism and lifestyle factors associated with bone mass in Japanese female college students.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studies have found associations between vitamin D pathway gene polymorphisms and circulating 25(OH)D level. 79 Genetic variants in vitamin D pathway genes, namely in the vitamin D nuclear receptor ( VDR ) gene, have been associated with obesity in some, 1013 but not all studies. 14,15 Studies of other genes in the vitamin D pathway, including vitamin D binding protein ( DBP ) or group-specific component ( GC ) or CYP27B1 and BMI, have also produced inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of the BsmI AA and TaqI CC genotypes on bone mass in Japanese women have rarely been examined because these genotypes are present at a relatively lower proportion than that seen in European countries; e.g., the respective allelic frequencies for the BsmI genotype G and A in the European population were 59% and 41%, respectively, compared to 88% and 12% in the Japanese population, (25,30), indicating a clear racial difference. In previous studies, less than 200 Japanese women participants were observed, a few of whom expressed the BsmI AA and TaqI CC genotypes (n = 0-2); hence, the relevant data could not be included in the analyses (20,21,(31)(32)(33). However, in the present study involving 499 participants, these genotypes were recognized (n = 8 for both) and included in the analysis.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, there are relatively fewer studies that assessed the relationship among bone mass, VDR gene polymorphisms, and environmental factors in premenopausal Japanese women. In these studies, the number of participants was low, and their age range was relatively wide (18-44 years) (19)(20)(21). Estrogen levels and lifestyle factors among participants can vary if a wide age range is considered in a study.…”
Section: Introductionmentioning
confidence: 99%